Feasibility of Simple Oral Preparation Contrast-Enhanced CT Colonography (SOP-CE-CTC) Using Mannitol as a Neutral Oral Contrast Agent - Vinita Rathi (Thieme Medical and Scientific Publishers Pvt. Ltd., 2022)
Purpose This article prospectively assesses the feasibility of simple oral preparation contrast-enhanced computed tomography colonography (SOP-CE-CTC) using a large volume of oral 3% mannitol for good colonic distension along with mural and mucosal fold visualization. Methods A total of 100 patients in whom contrast CT abdomen was requested, recruited as per selection criteria, were advised to take mild oral bowel preparation for two nights, prior to the investigation. Then, after fasting overnight, they were asked to consume 1,500 to 2,000 mL of 3% mannitol solution in about an hour. Thirty minutes after completing the ingestion of oral mannitol, intravenous contrast was injected and SOP-CE-CTC was acquired at 55 seconds. Distension of six segments of the colon was evaluated by assigning scores 1 to 4 for qualitative assessment; and measuring the maximum luminal diameter of the colon, for quantitative assessment. Colonic mucosal and mural visualization were evaluated subjectively. All observations were recorded by two reviewers (with varying levels of experience) independently. Results On qualitative analysis, the colon showed optimal distension (score 4) in 58 to 89% cases on SOP-CE-CTC. There was agreement between both the reviewers in 89 to 99% cases (weighted kappa 0.820-0.979; p < 0.001). On quantitative analysis, the mean of the maximum colonic diameter ranged between 3.4 and 5.2 cm; and both the reviewers agreed in 89 to 97% cases (weighted kappa 0.777-0.967; p < 0.001). Mural and mucosal fold visualization in the proximal four segments of the colon was excellent (in 90-98%) but in the rectum and sigmoid it was 45 and 66%, respectively; both the reviewers agreed in 100% cases (weighted kappa 1.0 and p < 0.001). Conclusion Good colonic distension, mural, and mucosal fold visualization can be achieved on SOP-CE-CTC using 1,500 to 2,000 mL of 3% oral mannitol and mild oral bowel preparation agents.